Biorelevant In Vitro Skin Permeation Testing and In Vivo Pharmacokinetic Characterization of Lidocaine from a Nonaqueous Drug-in-Matrix Topical System - Greuber, Emileigh; Vought, Kip; Patel, Kalpana; Suzuki, Hiroaki; Usuda, Kazuhiro; Shiramizu, Akira; Koplowitz, Luana Pesco; Koplowitz, Barry; Maibach, Howard I.; Lissin, Dmitri (AAPS PharmSciTech, 2021)
Recently, lidocaine topical systems utilizing nonaqueous matrices have been developed and provide efficient lidocaine delivery through the skin, such that lower concentrations of drug provide equivalent or greater drug delivery than drug-in-matrix hydrogel lidocaine patches. This study characterizes drug delivery from a nonaqueous lidocaine topical system with increasing drug load both in vitro and in vivo . Topical systems formulated with either 1.8% or 5.4% lidocaine were applied to healthy volunteers’ backs ( n = 15) for 12 h in a single-center, open-label, four-treatment, four-period crossover pharmacokinetic study. Subjects were dosed with either three 1.8% systems or one, two, or three 5.4% systems in each period. Blood was collected for up to 48 h, and plasma lidocaine levels were measured with a validated HPLC method. In parallel, human and mouse skin models characterized the in vitro skin permeation profile. The pharmacokinetic profile was linear between one, two, and three lidocaine 5.4% applications. Application of three lidocaine 1.8% systems (108 mg lidocaine) was bioequivalent to one lidocaine 5.4% system (108 mg lidocaine). Both topical systems remained well adhered to the skin and irritation was mild. The 5.4% system had approximately threefold higher skin permeability than the 1.8% system in the mouse and human skin models. The results indicate increasing the drug load by three times results in triple the drug delivery both in vivo and in vitro . The relationship between the in vitro permeation and in vivo absorption correlates and is nonlinear.